1995
DOI: 10.1007/bf00029532
|View full text |Cite
|
Sign up to set email alerts
|

Influence of paclobutrazol on growth and yield of Brassica carinata A.Br.

Abstract: Foliar spraying of Brassica carinata (cv. PC 5) with paclobutrazol (PP 333) at 5, 10 and 20 pg ml-' concentrations, reduced plant height significantly and modified the canopy structure by enhancing the number of branches (primary, secondary and tertiary) and the angle of insertion of primary branches on the main axis. The seed yield per plant also increased mainly due to increase in the number of siliquae per plant. Paclobutrazol increased total dry matter of plants and partitioning coefficients. The leaves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
4
19
3
2
Order By: Relevance
“…At both stations it was observed that application of only triazole fungicides (Top0.5and Folicur + Proline) reduced oil content in comparison with control and other treatments [6,16]. Our results are contradicted by MertTürk et al (2008) [23] and Butkute et al (2006) [24], who worked with triazole fungicides Harvesan and Folicur, respectively, and reported that oil content of rapeseed increased significantly after triazole application in comparison with the control.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…At both stations it was observed that application of only triazole fungicides (Top0.5and Folicur + Proline) reduced oil content in comparison with control and other treatments [6,16]. Our results are contradicted by MertTürk et al (2008) [23] and Butkute et al (2006) [24], who worked with triazole fungicides Harvesan and Folicur, respectively, and reported that oil content of rapeseed increased significantly after triazole application in comparison with the control.…”
Section: Resultscontrasting
confidence: 87%
“…Triazole and strobilurin treatments, along with plant growth regulators, are associated with various morphological and physiological changes in various plants; including inhibition of plant growth, decrease in inter-nodal elongation, increased chlorophyll content, enlarged chloroplast, thicker leaf tissue, increased root to shoot ratio, delayed senescence, increased antioxidant potentials, and enhancement in alkaloid production [3,4]. For example, triazole fungicides affect the isoprenoid pathway and alter the levels of certain plant hormones by inhibiting gibberellin synthesis [5,6]. Triazole inhibits mono-oxygenases that results in oxidation of ent-kaurene to ent-kaurenoic acid in three steps, which is an early reaction in GA biosynthesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Spring applications of PBZ in oilseed rape (Brassica napus) prior to a period of rapid crop development reduced plant height, but they had an adverse effect on the yield components and they offered no practical advantage in the commercial production of oilseed rape (Scarisbrick et al, 1985). By contrast, foliar application of PBZ in Ethiopian mustard (Brassica carinata), apart from reducing plant height, increased seed yield per plant primarily due to an increase in the number of siliquae (i.e., pods) per plant and secondarily due to an increase in total dry matter of plants and partitioning coefficients (Setia et al, 1995). The shortening effect of PBZ on sunflower plants appeared to be associated with the application scheme tested.…”
Section: Resultsmentioning
confidence: 99%
“…1), and this is attributed to higher chlorophyll accumulation in leaves. Previous studies in different plants cultivars had shown leaves exhibited higher chlorophyll content when treated with PBZ (Setia et al, 1995;Bañón et al, 2002). A Study on Catharanthus roseus plant indicated that, the gibberellin biosynthesis inhibitor is capable of enhancing photosynthesis net assimilation rate and chlorophyll content (Abdul Jaleel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%